(untitled) (Reflection and Critique Law Magazine, 2022)
SUMMARY The Federal Constitution of 1988 innovated our homeland legal system by elevating the Principle of Human Dignity to a status superior to any other norm or principle. However, by making a historical and current analysis of the Brazilian Social Security system, we realize that such an institute, even though its guiding principle is the principle of the dignity of the human person, does not cover all those needy people, who in some way deserve protection. to have a minimum of dignity in their existence, as is the case of affective parents (stepmother / stepfather). The aim of this paper was to demonstrate the need to equate the affective parents with the biological parents, with regard to obtaining social security benefits such as the death pension, as a way to ensure them a dignified existence as required by our Major Charter, which became clear later on. of the points here exposed. Since it was not an objective to exhaust the subject in this simple work, it is hoped that it can serve as a starting point for a more intense discussion regarding the issues raised here.